The Semaglutide: A revolution in the treatment of obesity and prevention of cardiovascular disease - Bilska, Wiktoria; Żydek, Ada; Ciułek, Urszula; Paduch-Jakubczyk, Wiktoria; Dubińska, Michalina; Zduńczyk, Wiktoria; Dobosz, Anna (Quality in Sport, 2024)
Introduction and Objective: Obesity represents a significant public health concern in the 21st century, with a substantial burden of disease attributable to its complications, including type 2 diabetes, hypertension, and cardiovascular disease. The objective of this review is to evaluate the efficacy and safety of semaglutide, a GLP-1 receptor agonist, in the treatment of obesity and its impact on cardiometabolic risk factors. The Review and Methods: This review is based on an analysis of the scientific literature, including meta-analyses and clinical trials. The PubMed, Scopus and Web of Science databases were searched for publications up to 2023. Abridged Description of the State of Knowledge: The efficacy of semaglutide in reducing body weight in patients with obesity is supported by evidence from clinical trials. Its mechanism of action includes the delay of gastric emptying and the reduction of hunger. The drug has been demonstrated to exert a beneficial effect on the lipid profile and blood pressure, thereby reducing the risk of cardiovascular disease. The adverse effects, which are primarily gastrointestinal in nature, are typically mild and resolve with treatment. Summary: Semaglutide represents a promising therapeutic option for obese patients, offering an effective means of reducing body weight and improving cardiometabolic parameters. However, further studies are required to evaluate the long-term effects of this therapy and its application in different patient populations. Keywords: Semaglutide, obesity, weight reduction, GLP-1, cardiometabolic risk factors, drug treatment.